2018
DOI: 10.1002/hsr2.102
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of chest ultrasound in patients with pneumonia in the intensive care unit: A single‐hospital study

Abstract: Background and aimsChest radiography (CXR) and computerized tomography (CT) scan are the preferred methods for lung imaging in diagnosing pneumonia in the intensive care unit, in spite of their limitations. The aim of this study was to assess the performance of bedside lung ultrasound examination by a critical care physician, compared with CXR and chest CT, in the diagnosis of acute pneumonia in the ICU.Materials and MethodsThis was an observational, prospective, single‐center study conducted in the intensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
1
11
1
2
Order By: Relevance
“…In addition, it was found that the location of the lesions in each patient with LUS-positive was exactly consistent with that on CT after comparison. The inflammation lesions of two patients were fortunately distributed near the pleura, so ultrasound can determine the location and size [14,23]. As for blood-test results, one of nine patients (11.11%) showed elevated ALT and AST (164U/ L, 94U/L, normal value <40U/L).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, it was found that the location of the lesions in each patient with LUS-positive was exactly consistent with that on CT after comparison. The inflammation lesions of two patients were fortunately distributed near the pleura, so ultrasound can determine the location and size [14,23]. As for blood-test results, one of nine patients (11.11%) showed elevated ALT and AST (164U/ L, 94U/L, normal value <40U/L).…”
Section: Discussionmentioning
confidence: 97%
“…For example, it is quick, affordable, requires no ionizing radiation, can be done at the bedside, and it addresses many of the same clinical questions that chest radiography and CT scans address[ 123 ]. In fact, lung ultrasound has been shown to be more sensitive than traditional chest radiography in the detection of infections involving the lower respiratory tract[ 124 , 125 ]. POCUS can not only be useful in the initial diagnosis of COVID-19, but it is also useful in following disease progression and monitoring for many of the associated complications[ 34 ].…”
Section: Evolving Trends and Future Directionsmentioning
confidence: 99%
“…11,12 In the ICU setting, LUS was superior to chest X-ray in detecting pneumonia. 13 Although CXR has poor sensitivity and specificity compared to chest CT and LUS, it remains the standard protocol for diagnosing the disease. Plain radiographs can miss up to 40% of confirmed COVID-19 cases due to the nature of the disease, in which lesions are peripherally distributed, and pathology is evident primarily in the terminal alveoli and close to the pleural interface.…”
Section: Resultsmentioning
confidence: 99%